2017
DOI: 10.1186/s12937-017-0288-8
|View full text |Cite
|
Sign up to set email alerts
|

Weekday snacking prevalence, frequency, and energy contribution have increased while foods consumed during snacking have shifted among Australian children and adolescents: 1995, 2007 and 2011–12 National Nutrition Surveys

Abstract: BackgroundThere are limited data on the evolution of eating habits, including snacking, in Australia. This study aimed to understand snacking trends among Australian children over three previous National Nutrition Surveys.MethodsData were analysed from a single weekday 24-h recall in the National Nutrition Surveys 1995, 2007, 2011–12 among children 2-16y (n = 8258). A snacking occasion was defined as an eating occasion that occurred between meals based on time of day.ResultsThe percentage of children snacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 74 publications
3
42
0
Order By: Relevance
“…American children snack 2–3 times per day and snacking contributes 24% of their daily energy intakes [ 2 ]. A similar scenario was reported in Australia [ 3 ], with about 96% of children and adolescents reported consuming snacks in the 2011–2012 national survey, representing 30.5% of total daily energy intake. In contrast, the situation in China is quite different.…”
Section: Introductionsupporting
confidence: 76%
“…American children snack 2–3 times per day and snacking contributes 24% of their daily energy intakes [ 2 ]. A similar scenario was reported in Australia [ 3 ], with about 96% of children and adolescents reported consuming snacks in the 2011–2012 national survey, representing 30.5% of total daily energy intake. In contrast, the situation in China is quite different.…”
Section: Introductionsupporting
confidence: 76%
“…Additionally, a comparison between data collected through the National Diet and Nutrition Survey (NDNS) and data from a Northern Irish cohort of adolescents demonstrated significant increases in the percentage of energy intake from snacks (29.8% in 1997 vs. 32.5% in 2005), the portion size consumed, and the frequency of snack consumption over an 8-year period [12]. Similar trends were also observed in Australia, where the percentage of children and adolescents snacking (92.5% in 1995 vs. 95.8 % in 2011–2012), mean number of snacking occasions (2.0 in 1995 vs. 2.5 in 2011–2012), and the energy contribution from snacking (24.1% in 1995 vs. 30.5% in 2011–2012) increased over time [11].…”
Section: Introductionsupporting
confidence: 59%
“…Recent studies suggest that total energy intake has increased over the past few decades, with shifts away from meals to snacks [9,10]. The snacking prevalence, the frequency of daily snack consumption, and the contribution of snacks to daily energy intake have substantially increased in all age groups in different parts of the world [11,12,13]. Surveys conducted in the United States revealed that the prevalence of snack consumption over a 2-day period has dramatically increased among American adults from 71% in 1977 to 97% in 2003–2006.…”
Section: Introductionmentioning
confidence: 99%
“…Snacking is a prominent dietary habit in most parts of the world and has increased over time in prevalence, frequency, portion size, and energy contribution, especially among high-income countries (HICs) [1][2][3]. In the United States, for example, the prevalence of snack consumption (from 71 to 97%), the number of snacks consumed per day (from 1.26 to 2.23), and the percentage of daily energy provided by snacks (from 18 to 24%) dramatically increased among adults from 1977 to 2003-2006 [1].…”
Section: Introductionmentioning
confidence: 99%